Art Music by Caribbean Composers: St. Kitts and Nevis - Gangelhoff, Christine; LeGrand, Cathleen (International Journal of Bahamian Studies, 2013)
Steel pans, arriving from Trinidad in the 1940s, quickly became popular and a wealth of steel bands proliferated (Cramer-Armony & Robinson, 2008). Steel bands became “the musical ensemble of choice for public dances and private parties, concerts and street jamming, displacing the pre-eminence of the horn-based orchestra, the String Band which had always been few in numbers, and the Big Drum” (Armony, n.d., para. 20). The annual St. Kitts Music Festival, held during the summer, brings international popular and jazz musical artists to Basseterre. On Nevis, a new Performing Arts Center (opened in 2012) provides performance and rehearsal space for a variety of performing artists and, it is hoped, will help “to raise the bar of excellence in the arts” (Washington, 2012, para. 6).